2022
DOI: 10.1021/acs.nanolett.1c04665
|View full text |Cite
|
Sign up to set email alerts
|

Interior and Edge Magnetization in Thin Exfoliated CrGeTe3 Films

Abstract: CrGeTe 3 (CGT) is a semiconducting vdW ferromagnet shown to possess magnetism down to a two-layer thick sample. Although CGT is one of the leading candidates for spintronics devices, a comprehensive analysis of CGT thickness dependent magnetization is currently lacking. In this work, we employ scanning SQUID-on-tip (SOT) microscopy to resolve the magnetic properties of exfoliated CGT flakes at 4.2 K. Combining transport measurements of CGT/NbSe 2 samples with SOT i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 45 publications
1
24
0
Order By: Relevance
“…Layered vdW tellurides including CrSiTe 3 and CrGeTe 3 , 16–19 Fe 3 AsTe 2 , 20 Fe 3 GeTe 2 , 21,22 Fe 5 AsTe 2 , 23,24 Fe 5 GeTe 2 , 5,15,25–27 and TaFe 1+ x Te 3 28,29 are promising for the design of novel spintronic devices with tailored functionalities. The latter compound is distinguished by the peculiar crystal structure and interesting physical properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Layered vdW tellurides including CrSiTe 3 and CrGeTe 3 , 16–19 Fe 3 AsTe 2 , 20 Fe 3 GeTe 2 , 21,22 Fe 5 AsTe 2 , 23,24 Fe 5 GeTe 2 , 5,15,25–27 and TaFe 1+ x Te 3 28,29 are promising for the design of novel spintronic devices with tailored functionalities. The latter compound is distinguished by the peculiar crystal structure and interesting physical properties.…”
Section: Introductionmentioning
confidence: 99%
“…11 At the same time, Fe 5 GeTe 2 , which is ferromagnetic below 310 K, 5,[12][13][14] shows the efficient spin filtering within the Fe 5 GeTe 2 /graphene heterostructure already at room temperature. 15 Layered vdW tellurides including CrSiTe 3 and CrGeTe 3 , [16][17][18][19] Fe 3 AsTe 2 , 20 Fe 3 GeTe 2 , 21,22 Fe 5 AsTe 2 , 23,24 Fe 5 GeTe 2 , 5,15,[25][26][27] and TaFe 1+x Te 3 28,29 are promising for the design of novel spintronic devices with tailored functionalities. The latter compound is distinguished by the peculiar crystal structure and interesting physical properties.…”
Section: Introductionmentioning
confidence: 99%
“…The vanishing remnant magnetization in zero field with increasing thickness is a phenomenon common to a number of vdW ferromagnetic materials. For example, thin CrGeTe 3 (CGT) films ( d < 10 nm) exhibit a net magnetization at zero applied field. , In contrast, using SQUID-on-tip (SOT) microscopy and in situ magneto-transport measurements of CGT/NbSe 2 bilayers, recent work demonstrated that the interior of thicker flakes ( d > 10 nm) has zero remnant field, with hard FM appearing only at the sample edge . This CGT edge magnetization is confined to a magnetic nanowire with a width and thickness of a few tens of nanometers.…”
Section: Introductionmentioning
confidence: 99%
“…The fact that the hysteresis loop maintains its direction, or that the AHE (Δ R xy ) does not change its sign, even when the Hall coefficient changes the sign or dominant carrier type is changed is a significant observation, as it rules out the trivial Hall effect due to any stray magnetic field produced by the ferromagnet (CGT) as a possible cause for the R xy hysteresis (in the trivial Hall effect scenario the hysteresis or Δ R xy would also change sign when the main carrier type or Hall slope changes sign). , Furthermore, we have estimated that the strength of the fringe magnetic field in such devices (no more than 1 mT , ) is too weak to produce the observed Δ R xy (of ∼10 Ω, which would require a change in magnetic field on the order 0.1 T, as seen in Figure d).…”
mentioning
confidence: 99%
“…For the topological insulator, we employ flakes exfoliated from a single crystal of BiSbTeSe 2 (BSTS) grown by the vertical Bridgman technique as described in ref . Taking advantage of the layered nature of these crystals, it is possible to assemble heterostructures while avoiding those defects and irregularities in the interface that might occur in heterostructures assembled via growth due to lattice mismatch and chemical diffusion (both issues can be detrimental for AHE observation). , We chose topological insulator flakes with a thickness in the range of 40–70 nm, which maintain the intrinsic insulating bulk and conduct mainly through the surface states. ,, For the ferromagnetic insulator, we chose flakes with a thickness in the range of 4–10 nm, whose low temperature magnetization shows a more rectangular hysteresis loop with a clear coercivity and higher remnant magnetization compared to the smooth magnetization behavior for bulk CGT and the more complicated hysteresis loops with softer magnetic behavior in thicker CGT flakes (>10 nm) . The latter are usually attributed to the formation of labyrinth type domains , (see Figure S1 for an evolution of hysteresis loops of CGT as thickness is increased, measured using Magneto Optics Kerr Effect).…”
mentioning
confidence: 99%